The Implementation of Comic Books to Increase the Learning Motivation of Primary School Students - Harni, Harni; Murwaningsih, Tri; Sukarno, Sukarno (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
This study was motivated by the fact that student learning motivation is still relatively low due to the use of learning media that is not varied and not interesting. This study aims to increase elementary school students' learning motivation through the implementation of comic media in learning. This study is a Classroom Action Research (CAR) conducted in class V of SDN 03  Gedong in the first semester of the 2025/2026 academic year. The research subjects were 25 students. The research was conducted in two cycles, each of which included the stages of planning, implementation of actions, observation, and reflection. Data collection techniques used observation, learning motivation questionnaires, and documentation. The data were analyzed descriptively, qualitatively, and quantitatively. The results showed that the use of comic media could increase student learning motivation. The percentage of student learning motivation increased from 56% in the pre-cycle to 69% in Cycle I and increased again to 82% in Cycle II. Based on these results, it can be concluded that comic media is effective in increasing the learning motivation of elementary school students.